Designing Multicultural-Based Contextual Learning Model in Teaching Writing at Chandra Kumala Senior High School - Freddy Nababan; Sondang Manik; Dorayanti Lumban Gaol; Ester Donna Simanjuntak (Cetta: Jurnal Ilmu Pendidikan, 2019)
This research is about designing learning model and part of a R&D research (Research and Development), which aims to; (1) describe the design of Multicultural-Based Contextual Learning Model (MBCLM) at SMAS Chandra Kumala, Deliserdang, (2) find out the effect of Multicultural-Based Contextual Learning Model (MBCLM) to students’ learning at SMAS Chandra Kumala, Deliserdang.This research was designed by incorporating an Authenticity-Centered Approach (ACA) principles proposed by Mishan which focus on the authenticity of learning material. Authenticity needed because it links to students’ contextual or daily lives. The method of this study was qualitative and quantitative research. The design and learning material were validated by two validators. The subject in this study was the students of class XI-A and C senior high school at Chandra Kumala. The instruments used to collect data were questionnaires, syllabus, lesson plan and adjudication sheets of the writing test. The data collector in the form of a questionnaire used Likert scale. The results of this research suggested that the design and learning material produced a very good result where the percentage of them exceeding the minimal standard of percentage criteria (or >75%), while the result of the t-test (by applying Multicultural-Based Contextual Learning Model) showed that the t observed is higher than t table (5.57 ˃ 1.671) at the level of significance of 0.05. Thus, it can be concluded that teaching writing by applying Multicultural-Based Contextual Learning Model affects the students’ writing competence